Diagnosis and management of lip filler complications - a case study with literature review - Laura Wojtala; Kamil Kapłon; Weronika Pawłocik; Julia Szymańska; Weronika Pawlak; Agnieszka Możdżyńska; Lena Musiał; Anna Rymarz; Izabela Kamińska; Ewa Grabowska (Kazimierz Wielki University, 2023)
Introduction Aesthetic medicine treatments are becoming more popular in the 21st century due to the changing beauty standards and the treatments' ability to help slow down the aging process. One of the most asked for treatments is a lip filler using hyaluronic acid. The popularity and frequency of the said treatment are directly connected to the rising number of complications in this area. The right diagnosis of lip filler complications allows to implement correct management and therefore therapeutic success for the patient. The aim The aim of the work was to analyze and discuss patient's complications and implemented medical management after lip filler treatment using hyaluronic acid. Case report An individual case study that included clinical examination, medical and photographic documentation analysis. Results The patient was diagnosed with one of the most common complications after lip filler which is swelling. The swelling was a result of an allergic reaction and was classified as severe. Medical management using corticosteroid and antihistamines was implemented with a good therapeutic outcome. Conclusions Implemented management using corticosteroids and antihistamines for severe swelling after lip filler is effective. Due to the rising number of treatments using soft tissue fillers, it is expected that more patients will present with complications after aesthetic medicine procedures.